Defining and exploring relational inclusivity: attending to inclusion across four dimensions of schooling - Mamas, Christoforos; Trautman, David (Frontiers in Education, 2025)
The goal of this paper is to present, conceptually and empirically, a framing for inclusion grounded in the social network perspective: Relational Inclusivity (RI). This approach emphasizes the importance of interdependent student relationships that educators must attend to in order to create socially responsive learning communities. We center relational ties and dynamics across four social dimensions experienced by students: friendships, recess, academic support, and emotional connection networks. Using data from a Grade 7 class collected through the Social Network Analysis (SNA) Toolkit, we illustrate how student experiences vary across these four dimensions and how educators may attend to them. We argue that an RI approach necessarily shifts attention away from traditional individualized paradigms of achievement and towards the social dynamics of learning environments.